APLIKASI METODE MEAN DAN MEDIAN ABSOLUTE DEVIATION PADA DATA ELEKTROMAGNET SEBAGAI PREKURSOR GEMPA BUMI DI PELABUHAN RATU - Sulastri Sulastri; Supriyanto Rohadi; Bambang Sunardi; Aprilia Nur Vita; Angga Setiyo Prayogo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Electromagnetic anomalies can be used in detecting the presence of earthquake precursors. This study aimed to obtain appropriate statistical methods of electromagnetic data processing in Pelabuhan Ratu. The mean and median absolute deviation methods were applied to electromagnetic data of Pelabuhan Ratu from January to November 2016. The electromagnetic anomaly will be investigated in Hz/Hh and Hh/Hht polarization ratios and E/H electromagnetic impedance. To determine whether the anomaly is an earthquake precursor or due to a magnetic storm, it is necessary to look at Dst index data on the corresponding date. There were electromagnetic anomalies in both applied methods, either as earthquake precursors or due to magnetic storms, with anomalies in E/H electromagnetic impedance that were not significant. The median absolute deviation gave better results than the mean absolute deviation in the identification of electromagnetic anomalies existence. Thus, the median absolute deviation is more suitable to be applied to processing of electromagnetic data as an earthquake precursor in Pelabuhan Ratu.Keywords: electromagnetic anomaly, earthquake precursor, mean, median.